STRUCTURAL GEOLOGY FAULT EFFECT ON HIGHWALL COAL MINING AND FAILURE EVALUATION BASED ON VELOCITY DATA AT BENGALON, EAST-KUTAI DISTRIC, EAST KALIMANTAN PROVINCE. - Muh Arif Idhan; Gina Audina Alhabsyi; Muhammad Ikbal (PERHAPI, 2021)
The geological structure especially folds and faults will reduce slope stability at slope mining where many events are the main factors that trigger slope failure. The geological structure